The Influence of Emotional Intelligence on the Learning Motivation of Akidah Akhlak Students at Madrasah Aliyah Muhammadiyah Padaelo - Mansur, Sulkifli (IAIN Parepare, 2024)
This study aims to determine the level of emotional intelligence among students at MA Muhammadiyah Padaelo, Tanete Rilau Subdistrict, Barru Regency; the level of learning motivation in Aqidah Akhlak subjects; and the relationship between emotional intelligence and students learning motivation. This research employed a quantitative method with a field research approach, where the researcher directly observed the students. Data analysis techniques included instrument validity and reliability tests.The results of the study revealed that: (1) Emotional intelligence among students at MA Muhammadiyah Padaelo falls into the good category; (2) Students learning motivation is also in the good category based on the questionnaire results; (3) There is a significant relationship between emotional intelligence and learning motivation at a 5% significance level (rxy > Rtabel = 0.320) and a 1% significance level (rxy > Rtabel = 0.413). Therefore, the null hypothesis (H0) is rejected, and the alternative hypothesis (Ha) is accepted. The findings indicate that students learning motivation is influenced by emotional intelligence by 79.32%, while the remaining 20.68% is affected by other factors. Keywords: Emotional Intelligence, Learning Motivation.